Comparison of the Effectiveness of Emotion Regulation-Based Therapy and Unified Transdiagnostic Treatment on Cognitive Insight in Women Engaged in Emotional Divorce with Early Marriage - Rastgar, AbdolHamid; Yousefi, Emad; Khajehpour, Leila (Psychology of Woman Journal, 2024)
Objective: The objective of this study was to compare the effectiveness of emotion regulation-based therapy and unified transdiagnostic therapy on cognitive insight in women engaged in emotional divorce with early marriage. Methods and Materials: This quasi-experimental research employed a pre-test and post-test control group design. The sample consisted of 45 women involved in emotional divorce, diagnosed by psychologists at counseling centers in Shiraz, and were selected through convenience sampling. Participants were randomly assigned to three groups: one control group (n=15) and two experimental groups (n=30). The experimental groups received either emotion regulation-based therapy or unified transdiagnostic therapy. Data were collected using Beck’s Cognitive Insight Questionnaire (BCIS) and analyzed using SPSS (version 26) through descriptive statistics and Multivariate Analysis of Covariance (MANCOVA). Findings: The results indicated that both unified transdiagnostic therapy and emotion regulation-based therapy were effective in increasing cognitive insight in women engaged in emotional divorce with early marriage. The post-test scores showed significant improvement compared to the pre-test scores in the experimental groups, while the control group showed little change. The analysis revealed significant differences in cognitive insight components (self-reflectiveness and self-certainty) between the experimental and control groups. However, there was no significant difference in the effectiveness between the two therapeutic methods. Conclusion: This study highlights the importance of employing these therapeutic approaches in counseling centers to improve cognitive insight and other psychological variables in women with early marriages.